Modelling and Control of Grid-Connected PV–Battery Hybrid System Using Dynamic Voltage Restorer for Enhanced Power Quality - Sritam Parida; Maheswar Prasad Behera; Manoj Kumar Sahu (International Journal of Electrical Power and Machine Systems, 2025)
The integration of large-scale photovoltaic (PV) systems into modern power grids introduces significant challenges in maintaining power quality, including voltage sags, swells, and harmonics. To address these issues, this study presents a comprehensive modelling and control framework for a grid-connected PV–Battery hybrid system equipped with a Dynamic Voltage Restorer (DVR). The PV array is modelled using detailed mathematical equations, while the DC–DC converter incorporates advanced Maximum Power Point Tracking (MPPT) algorithms to optimize energy extraction under variable irradiance conditions. The inverter and grid interconnection are modelled to assess system stability, and the DVR is designed to compensate for voltage disturbances using a PI controller. MATLAB/Simulink simulations are performed to validate the system performance under different operating scenarios. The proposed hybrid system demonstrates improved voltage regulation, reduced power quality disturbances, and enhanced reliability of renewable energy integration into the grid. The study also lays the foundation for implementing intelligent control strategies and energy storage coordination in future smart grid applications.
Keywords: Dynamic Voltage Restorer (DVR); Grid-Connected Photovoltaics; MATLAB/Simulink Modelling; Maximum power point tracking (MPPT); PI controller; PV–Battery Hybrid System; Power Quality Enhancement; renewable energy integration